CERDAS MENGGUNAKAN INTERNET DI MASA PANDEMI COVID-19 - Thresia Hilda Mathelda Yenkase Krey; Winna Amelia Alfrida Senandi (LPPM Uncen, 2023)
This activity is a form of application of science and technology which is carried out through counseling entitled